In Vivo Availability of Cannabinoid 1 Receptor Levels in Patients with First-Episode Psychosis - Borgan F.; Laurikainen H.; Veronese M.; Marques T.R.; Haaparanta-Solin M.; Solin O.; Dahoun T.; Rogdaki M.; Salokangas R.K.R.; Karukivi M.; Di Forti M.; Turkheimer F.; et al. (American Medical Association, 2022)
Importance: Experimental and epidemiological studies implicate the cannabinoid 1 receptor (CB1R) in the pathophysiology of psychosis. However, whether CB1R levels are altered in the early stages of psychosis and whether they are linked to cognitive function or symptom severity remain unknown.
Objective: To investigate CB1R availability in first-episode psychosis (FEP) without the confounds of illness chronicity or the use of illicit substances or antipsychotics.
Design, Setting, and Participants: This cross-sectional, case-control study of 2 independent samples included participants receiving psychiatric early intervention services at 2 independent centers in Turku, Finland (study 1) and London, United Kingdom (study 2). Study 1 consisted of 18 volunteers, including 7 patients with affective or nonaffective psychoses taking antipsychotic medication and 11 matched controls; study 2, 40 volunteers, including 20 antipsychotic-naive or antipsychotic-free patients with schizophrenia or schizoaffective disorder and 20 matched controls. Data were collected from January 5, 2015, through September 26, 2018, and analyzed from June 20, 2016, through February 12, 2019.
Main Outcomes and Measures: The availability of CB1R was indexed using the distribution volume (VT, in milliliters per cubic centimeter) of 2 CB1R-selective positron emission tomography radiotracers: fluoride 18–labeled FMPEP-d2 (study 1) and carbon 11–labeled MePPEP (study 2). Cognitive function was measured using the Wechsler Digit Symbol Coding Test. Symptom severity was measured using the Brief Psychiatric Rating Scale for study 1 and the Positive and Negative Syndrome Scale for study 2.
Results: A total of 58 male individuals were included in the analyses (mean [SD] age of controls, 27.16 [5.93] years; mean [SD] age of patients, 26.96 [4.55] years). In study 1, 7 male patients with FEP (mean [SD] age, 26.80 [5.40] years) were compared with 11 matched controls (mean [SD] age, 27.18 [5.86] years); in study 2, 20 male patients with FEP (mean [SD] age, 27.00 [5.06] years) were compared with 20 matched controls (mean [SD] age, 27.15 [6.12] years). In study 1, a significant main effect of group on [18F]FMPEP-d2 VT was found in the anterior cingulate cortex (ACC) (t16 = −4.48; P < .001; Hedges g = 1.2), hippocampus (t16 = −2.98; P = .006; Hedges g = 1.4), striatum (t16 = −4.08; P = .001; Hedges g = 1.9), and thalamus (t16 = −4.67; P < .001; Hedges g = 1.4). In study 2, a significant main effect of group on [11C]MePPEP VT was found in the ACC (Hedges g = 0.8), hippocampus (Hedges g = 0.5), striatum (Hedges g = 0.4), and thalamus (Hedges g = 0.7). In patients, [11C]MePPEP VT in the ACC was positively associated with cognitive functioning (R = 0.60; P = .01), and [11C]MePPEP VT in the hippocampus was inversely associated with Positive and Negative Syndrome Scale total symptom severity (R = −0.50; P = .02).
Conclusions and Relevance: The availability of CB1R was lower in antipsychotic-treated and untreated cohorts relative to matched controls. Exploratory analyses indicated that greater reductions in CB1R levels were associated with greater symptom severity and poorer cognitive functioning in male patients. These findings suggest that CB1R may be a potential target for the treatment of psychotic disorders.